Prediction of interacting motifs within the protein subunits of Picornavirus capsids - Ross, Caroline Jane (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
The Picornaviridae family contains a number of pathogens which are economically important including Poliovirus, Coxsakievirus, Hepatitis A Virus, and Foot-and-Mouth-Disease-Virus. Recently the emergence of novel picornaviruses associated with gastrointestinal, neurological and respiratory diseases in humans has been reported. Although effective vaccines for viruses such as FMDV, PV and HAV have been developed there are currently no antivirals available for the treatment of picornavirus infections. Picornaviruses proteins are classified as: the structural proteins VP1, VP2, VP3 and VP4 which form the subunits of the viral capsid and the replication proteins which function as proteases, RNA-polymerases, primers and membrane binding proteins. Although the host specificity and viral pathogenicity varies across members of the family, the icosahedral capsid is highly conserved. The capsid consists of 60 protomers, each containing a single copy of VP1, VP2 and VP3. A fourth capsid protein, VP4, resides on the internal side of the capsid. Capsid assembly is integral to life-cycle of picornaviruses; however the process is complex and not fully-understood. The overall aim of the study was to broaden the understanding of the evolution and function of the structural proteins across the Picornaviridae family. Firstly a comprehensive analysis of the phylogenetic relationships amongst the individual structural proteins was performed. The functions of the structural proteins were further investigated by an exhaustive motif analysis. A subsequent structural analysis of highly conserved motifs was performed with respect to representative enteroviruses, Foot-and-Mouth-Disease-Virus and Theiler's Virus. This was supplemented by the in silico prediction of interacting residues within the crystal structures of these protomers. Findings in this study suggest that the capsid proteins may be evolving independently from the replication proteins through possible inter-typic recombination of functional protein regions. Moreover the study predicts that protomer assembly may be facilitated through a network of multiple subunit-subunit interactions. Multiple conserved motifs and principle residues predicted to facilitate capsid subunit-subunit interactions were identified. It was also concluded that motif conservation may support the theory of inter-typic recombination between closely related virus sub-types. As capsid assembly is critical to the viral life-cycle, the principle interacting motifs may serve as novel drug targets for the antiviral treatment of picornavirus infections. Thus the findings in the study may be fundamental to the development of treatments which are more economically feasible or clinically effective than current vaccinations.
Keywords: Picornaviruses; Antiviral agents; Poliovirus; Coxsackieviruses; Hepatitis A virus; Foot-and-mouth disease virus; Viral proteins